2020
DOI: 10.1111/1759-7714.13281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and treatment recommendations for immune checkpoint inhibitor‐related hematological adverse events

Abstract: Immune checkpoint inhibitors (ICIs) are able to reactivate the immune system, thereby enhancing the anti‐tumor effects. However, over‐activated T cells may induce immune‐related adverse events (irAEs). Hematological irAEs are rarely reported which mainly represent monolineage cytopenia or pancytopenia, including autoimmune hemolytic anemia (AIHA), immune thrombocytopenia (ITP), neutropenia and aplastic anemia, sometimes even life‐threatening diseases such as hemophagocytic lymphohistiocytosis. Here, the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In a meta-analysis of 9324 patients, the frequency of neutropenia was smaller than 1%. 88 Previously reported reactivation of viral infections (ie, cytomegalovirus, hepatitis B) under ICI therapy were mostly observed following immunosuppressive treatment of irAEs. Hence, it does not appear reasonable to assume that patients undergoing ICI are at higher risk of becoming infected by SARS-COV-2 or other infectious agents compared with patients without ICI treatment.…”
Section: Covid-19mentioning
confidence: 99%
“…In a meta-analysis of 9324 patients, the frequency of neutropenia was smaller than 1%. 88 Previously reported reactivation of viral infections (ie, cytomegalovirus, hepatitis B) under ICI therapy were mostly observed following immunosuppressive treatment of irAEs. Hence, it does not appear reasonable to assume that patients undergoing ICI are at higher risk of becoming infected by SARS-COV-2 or other infectious agents compared with patients without ICI treatment.…”
Section: Covid-19mentioning
confidence: 99%
“…Of note, the accurate mechanism of TRAEs occurrence during this treatment (anti-angiogenesis-related or immune-related) can differ owing to individual differences. For instance, both drugs may lead to thrombocytopenia, which may be a consequence of anti-angiogenic agent-induced thrombotic microangiopathy and atypical hemolytic uremic syndrome or ICIs-induced overactivation of T cells ( 165 167 ). According to those reports, the treatment-related thrombocytopenia diminished with the discontinuation of agents or intravenous monoclonal antibodies (e.g., eculizumab) from the perspective of anti-angiogenesis therapy, or with the application of corticosteroids or immunosuppressive drugs from the perspective of ICIs therapy.…”
Section: Safety Of Combination Therapy Of Anti-angiogenic Agents Andmentioning
confidence: 99%
“…On the whole, a higher incidence has been reported with CTLA-4 inhibitors (i.e., ipilimumab) versus PD-1 inhibitors (i.e., pembrolizumab and nivolumab) and their association increased the risk. At variance, hematologic adverse events seem more frequent after PD-1 inhibitors and are mainly unilineage cytopenia, or bilineage cytopenia, whilst AH, TTP, eosinophilia, LGL, and hemophagocytic lymphohistiocytosis are rare [ 106 , 107 ]. A meta-analysis of 9324 patients indicated that the incidence of anemia, thrombocytopenia, and neutropenia was 9.8%, 2.8%, and 0.94%, respectively [ 106 ], with AIHA possibly having a fulminant course.…”
Section: Autoimmune Complications Associated With Old and New Antimentioning
confidence: 99%